2021
DOI: 10.1002/alr.22781
|View full text |Cite
|
Sign up to set email alerts
|

Integrated miRNA and mRNA expression profiling reveals dysregulated miRNA‐mRNA regulatory networks in eosinophilic and non‐eosinophilic chronic rhinosinusitis with nasal polyps

Abstract: Background: The precise mechanisms underlying pathogenesis of different subtypes of chronic rhinosinusitis with nasal polyps (CRSwNP) are still unclear.Emerging evidence indicates that microRNAs may play a role in the pathogenesis of CRSwNP. This study aimed to identify the dysregulated microRNA-messenger RNA (miRNA-mRNA) regulatory networks in eosinophilic (E) and noneosinophilic (non-E) CRSwNP. Methods: Whole-transcriptome sequencing was performed on nasal tissues of patients with ECRSwNP and non-ECRSwNP, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Moreover, miR‐125b‐5p, miR‐100‐5p, miR‐182, miR‐22, miR‐146a‐5p, and miR‐206 have been reported to be highly enriched in MSC‐derived exosomes/EVs 151–154 . Among them, miR‐146a‐5p, miR‐125b‐5p, and miR‐223 are associated with the regulation of type 2 inflammation in the nasal mucosa 155–160 . Further, miR‐146a‐5p has been reported to ameliorate allergic airway inflammation by targeting various genes in different cells.…”
Section: Immunomodulation Mechanisms Of Msc‐based Therapymentioning
confidence: 99%
“…Moreover, miR‐125b‐5p, miR‐100‐5p, miR‐182, miR‐22, miR‐146a‐5p, and miR‐206 have been reported to be highly enriched in MSC‐derived exosomes/EVs 151–154 . Among them, miR‐146a‐5p, miR‐125b‐5p, and miR‐223 are associated with the regulation of type 2 inflammation in the nasal mucosa 155–160 . Further, miR‐146a‐5p has been reported to ameliorate allergic airway inflammation by targeting various genes in different cells.…”
Section: Immunomodulation Mechanisms Of Msc‐based Therapymentioning
confidence: 99%
“…miR-221 is also upregulated in CRSwNP and may be directly implicated in cell cycle, apoptosis, and inflammation ( Bu et al, 2021 ; Silveira et al, 2021 ). Bu et al (2021) have found the expression of miR-449a is higher in non-ECRSwNP samples, compared with that in ECRSwNP samples and healthy controls, and this change involves adenosine monophosphate-activated protein kinase (AMPK), Rap1, and the ErbB-signaling pathway, all regulators in neutrophil activity and neutrophilic inflammation. Meanwhile, Silveira et al (2021) have also reported a higher level of miR-449a in CRSwNP group, compared with that in control group.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, miR-146a ( Xia et al, 2015 ), miR-614 ( Shin et al, 2020 ), and some other DE-miRs are also upregulated in CRS samples, highly through the pathway of mucin-type O-glycan biosynthesis ( Cha et al, 2021 ). Meanwhile, miR-3178, miR-585-3p, miR-3146, miR-320e, miR-142-3p, miR-154, miR-223, miR-205-5p, miR-222-3p, miR-378a-3p, miR-449b-5p, miR-22-3p, miR-21, miR-203a-3p, miR-677, miR-1037, and miR-79 are also overexpressed in CRSwNP samples ( Li et al, 2019c ; Xuan et al, 2019 ; Zhang et al, 2020b ; Bu et al, 2021 ; Qing et al, 2021 ; Silveira et al, 2021 ; He et al, 2022 ; Morawska-Kochman et al, 2022 ). Among them, miR-142-3p may regulate the inflammatory response through the lipopolysaccharide (LPS)-Toll-like receptor (TLR)-tumor necrosis factor-α (TNF-α) signaling pathway ( Qing et al, 2021 ); miR-3146 and miR-320e act in the mucin type O-glycan biosynthesis pathway in CRSwNP by targeting N-acetylgalactosaminyltransferase-like 6 (GALNTL6), N-acetylgalactosaminyltransferase 8 (GALNT8), and alpha-2,3-sialyltransferase 1 (ST3GAL1) genes ( Xuan et al, 2019 ); miR-223 plays in the mitogen-activated protein kinase (MAPK) signaling pathway ( Bu et al, 2021 ); miR-22-3p inhibits vascular endothelial (VE)-cadherin expression to regulate vascular permeability after binding to the specific site in the 3′-UTR of the human VE-cadherin mRNA ( Zhang et al, 2020b ); the TGF-β1-miR-21-PTEN-Akt axis may propel the EMT of CRSwNP ( Li et al, 2019c ); miR-677, miR-1037, and miR-79 may post-transcriptionally regulate gene expression in the Hippo signaling pathway ( He et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations